Michael Oakeshott's skepticism - Botwinick, Aryeh (Princeton monographs in philosophy., 2011)
The English philosopher Michael Oakeshott (1901-1990) is known as a conservative who rejected philosophically ambitious rationalism and the grand political ideologies of the twentieth century on the grounds that no human ideas have ultimately reliable foundations. Instead, he embraced tradition and habit as the guides to moral and political life. In this book, Aryeh Botwinick presents an original account of Oakeshott's skepticism about foundations, an account that newly reveals the unity of his thought.